Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1051/0004-6361/201424540
|View full text |Cite
|
Sign up to set email alerts
|

On the missing second generation AGB stars in NGC 6752

Abstract: In recent years the view of Galactic globular clusters as simple stellar populations has changed dramatically, it is now thought that basically all globular clusters host multiple stellar populations, each with its own chemical abundance pattern and colour-magnitude diagram sequence. Recent spectroscopic observations of asymptotic giant branch stars in the globular cluster NGC 6752 have disclosed a low [Na/Fe] abundance for the whole sample, suggesting that they are all first generation stars, and that all sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 66 publications
(141 reference statements)
12
55
1
Order By: Relevance
“…Campbell et al (2013) proposed that, in addition to He enhancement for the Na-rich stars, a substantial ad hoc increase in the mass-loss rate (20 times the RGB value) for NGC 6752 stars on the blue horizontal branch may be required to prevent further evolution up the AGB. However, Cassisi et al (2014) note that the required mass loss rate of ∼10 −9 M e yr −1 is several orders of magnitude higher than those allowed by current analyses of hot horizontal branch and B subdwarf stars. Additionally, horizontal branch simulations by Cassisi et al (2014) that accurately reproduce the R 2 parameter (N AGB /N HB ) for NGC 6752, M3, and M13, but do not invoke enhanced mass loss, also predict that ∼50% of NGC 6752ʼs AGB stars should be Na-rich (albeit with lower Y than the most extreme values).…”
Section: Interpreting the Agb And Rgb [Na Fe] Distributionsmentioning
confidence: 58%
See 1 more Smart Citation
“…Campbell et al (2013) proposed that, in addition to He enhancement for the Na-rich stars, a substantial ad hoc increase in the mass-loss rate (20 times the RGB value) for NGC 6752 stars on the blue horizontal branch may be required to prevent further evolution up the AGB. However, Cassisi et al (2014) note that the required mass loss rate of ∼10 −9 M e yr −1 is several orders of magnitude higher than those allowed by current analyses of hot horizontal branch and B subdwarf stars. Additionally, horizontal branch simulations by Cassisi et al (2014) that accurately reproduce the R 2 parameter (N AGB /N HB ) for NGC 6752, M3, and M13, but do not invoke enhanced mass loss, also predict that ∼50% of NGC 6752ʼs AGB stars should be Na-rich (albeit with lower Y than the most extreme values).…”
Section: Interpreting the Agb And Rgb [Na Fe] Distributionsmentioning
confidence: 58%
“…However, Cassisi et al (2014) note that the required mass loss rate of ∼10 −9 M e yr −1 is several orders of magnitude higher than those allowed by current analyses of hot horizontal branch and B subdwarf stars. Additionally, horizontal branch simulations by Cassisi et al (2014) that accurately reproduce the R 2 parameter (N AGB /N HB ) for NGC 6752, M3, and M13, but do not invoke enhanced mass loss, also predict that ∼50% of NGC 6752ʼs AGB stars should be Na-rich (albeit with lower Y than the most extreme values). These results indicate that enhanced mass loss for a particular subset of horizontal branch stars is unlikely to be the key link between RGB composition and post-RGB evolution.…”
Section: Interpreting the Agb And Rgb [Na Fe] Distributionsmentioning
confidence: 58%
“…However, in contrast to Campbell and collaborators, who concluded that in this GC all 2P stars fail to climb the AGB, we obtain that ∼74% of the AGB stars at 13 Gyr belong to the 2P with the current model assumptions. Cassisi et al (2014) also found a non-negligible proportion of 2P stars on the AGB (∼50%) thanks to synthetic horizontal branch simulations for NGC 6752. Theoretical works also emphasize the fact that the number of AGB stars in a given GC strongly depends on the assumptions made on the mass loss in the previous evolution phases Charbonnel & Chantereau 2016;Cassisi et al 2014).…”
Section: Asymptotic Giant Branchmentioning
confidence: 71%
“…Cassisi et al (2014) also found a non-negligible proportion of 2P stars on the AGB (∼50%) thanks to synthetic horizontal branch simulations for NGC 6752. Theoretical works also emphasize the fact that the number of AGB stars in a given GC strongly depends on the assumptions made on the mass loss in the previous evolution phases Charbonnel & Chantereau 2016;Cassisi et al 2014). Moreover, in the framework of the FRMS scenario, the theoretical Na spread on the AGB phase is a function of both age and metallicity (Charbonnel & Chantereau 2016), and the expected trends can explain the presence of 2P stars found in most of the GCs studied so far, which cover a range in age and iron content (47 Tuc, NGC 2808, M 3, M 5, M 13, M 55, M 2, see Johnson & Pilachowski 2012;García-Hernández et al 2015;Johnson et al 2015;Wang et al II, in prep.…”
Section: Asymptotic Giant Branchmentioning
confidence: 71%
“…Indeed, a change from 0.5 to 0.65 for η drastically 4 Campbell et al (2013) proposed fitting the sodium distribution along the AGB in NGC 6752 by assuming an increased mass loss rate by a factor of 20 on the HB for all 2P stars. This proposal, which would require mass loss rates of the order 10 −9 M yr −1 (i.e., significantly higher than current observational and empirical constraints) was carefully and critically discussed by Cassisi et al (2014).…”
Section: Theoretical Sodium Spread On the Agb As A Function Of Metallmentioning
confidence: 99%